Factors Associated with Maternal Deaths in District and Upazila Hospitals of Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): Aim of the study was to use death review to explore medical causes and three delay causal factors responsible for maternal deaths in district or below level health facilities of Bangladesh.Methods: Government health workers conducted facility based death review in 56 maternal deaths occurred during 2010-2012 in four district and five upazila (EmONC) health facilities of Bangladesh. The data was analyzed to assess the causal relationship between the medical causes and the three delays factors in maternal mortality.Results: Majority of the mothers died was young (89.3%; below age 30 years) and died during first pregnancy (78.6%) and postpartum period (71.4%). Postpartum hemorrhage and preeclampsia-eclampsia were the foremost causes of maternal deaths at district level facilities of Bangladesh. Seventy two percent of them arrived the hospitals in a travel time